Revisiting the Global Epidemiology of Cholera in Conjunction With the Genomics of Vibrio cholerae - Ramamurthy, Thandavarayan; Mutreja, Ankur; Weill, François-Xavier; Das, Bhabatosh; Ghosh, Amit; Nair, Gopinath Balakrish (Frontiers in Public Health, 2019)
Toxigenic Vibrio cholerae is responsible for 1.4 to 4.3 million cases with about 21,000–143,000 deaths per year. Dominance of O1 and O139 serogroups, classical and El tor biotypes, alterations in CTX phages and the pathogenicity Islands are some of the major features of V. cholerae isolates that are responsible for cholera epidemics. Whole-genome sequencing (WGS) based analyses of single-nucleotide polymorphisms (SNPs) and other infrequent genetic variants provide a robust phylogenetic framework. Recent studies on the global transmission of pandemic V. cholerae O1 strains have shown the existence of eight different phyletic lineages. In these, the classical and El Tor biotype strains were separated as two distinctly evolved lineages. The frequency of SNP accumulation and the temporal and geographical distribution supports the perception that the seventh cholera pandemic (7CP) has spread from the Bay of Bengal region in three independent but overlapping waves. The 2010 Haitian outbreak shared a common ancestor with South-Asian wave-3 strains. In West Africa and East/Southern Africa, cholera epidemics are caused by single expanded lineage, which has been introduced several times since 1970. The Latin American epidemics that occurred in 1991 and 2010 were the result of introductions of two 7CP sublineages. Sublineages representing wave-3 have caused huge outbreaks in Haiti and Yemen. The Ogawa-Inaba serotype switchover in several cholera epidemics are believed to be due to the involvement of certain selection mechanism(s) rather than due to random events. V. cholerae O139 serogroup is phylogenetically related to the 7CP El Tor, and almost all these isolates belonged to the multilocus sequence type-69. Additional phenotypic and genotypic information have been generated to understand the pathogenicity of classical and El Tor vibrios. Presence of integrative conjugative elements (ICE) with antibiotic resistance gene cassettes, clustered regularly interspaced short palindromic repeats-associated protein system and ctxAB promoter based ToxRS expression of cholera toxin (CT) separates classical and El Tor biotypes. With the availability of WGS information, several important applications including, molecular typing, antimicrobial resistance, new diagnostics, and vaccination strategies could be generated.